Gambaran Tingkat Kecemasan pada Perempuan Menopause di Junjung Buih III Palangka Raya - Nurul Chusna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Menopause is a period that sometimes makes some women experience physical and psychological disorders such as depression and so on. For some women, this period is also considered as the beginning of his nightmare in life. This study was conducted to see how the picture of anxiety levels in menopausal women is upheld in Junjung Buih III Palangkaraya foam. This study uses descriptive research design, namely research conducted with the main purpose of making an overview of the situation objectively. In retrieval of data using a cross-sectional time approach, namely the collection of data collected at certain times that can describe the situation in a certain time. The sample used in this study was menopausal women with 30 respondents. Anxiety in menopausal women is assessed by a questionnaire test with closed questions, respondents just choose alternative answers according to instructions, variations of the answers have been determined and arranged in advance so that respondents have the freedom to choose answers, The results of the study showed that the level of anxiety in menopausal women in Junjung Buih III Palangkaraya was moderate (50%).